Danmei Meets Fandom: A ‘Popularity Bubble’ - Wang, Aiqing (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2024)
In this article I illustrate the evolvement of the marginalised danmei (the Chinese equivalent of Japanese Boys Love) into a fandom-like subculture in contemporary China. I investigate danmei writers and their fanbases by analysing works and rankings on the leading female-oriented literature website Jinjiang and discussions on social media platforms represented by Weibo. Danmei writers are frequently correlated with (accused) overhyping and smear campaigns, and their fans contribute financially and in a form of maneuvring public discourse on social media, which is attributed to fangirls’ psychological and social pressure, as well as the prevailing capitalism and consumerism. Therefore, I argue that such a fandom-like phenomenon is only a ‘popularity bubble’, which by no means indicates an embracement of danmei as a literary genre and subculture or homosexuality as minority sexual orientation in China. Worse still, since some danmei fans demonstrate toxic fan practices such as cyber manhunt and online harassment and abuse, this ‘popularity bubble’ impinges upon danmei in a detrimental manner by imperilling its reputation and hindering its (fan) creation. To cite this article (7th APA style): Wang, A. (2024). Danmei meets fandom: A ‘popularity bubble’. Journal Communication Spectrum: Capturing New Perspectives in Communication 14(1), 1-10. https://doi.org/10.36782/jcs.v14i1.2417